Synergistic Effect, and Therapeutic Potential of Aqueous Prickly Pear Extract. In vivo Neuroleptic, Catatonic, and Hypoglycemic Activity - Benattia, Farah K.; Arrar, Zoheir; Dergal, Fayçal; Khabbal, Youssef (Current Chemical Biology, 2023)
Background: Prickly pear
Keywords: diabetes